The Effects of Gender and Career Stage on Ethical Judgment - Weeks, William A. (Journal of business ethics, 1999)
This article reports the findings of a survey examining if there are gender and career stage differences between male and female practitioners regarding ethical judgment. The results show that, on average, females adopted a more strict ethical stance than their male counterparts on 7 out of 19 vignettes. Males on the other hand, demonstrated a more ethical stance than their female counterparts on 2 out of 19 vignettes. The results furthermore indicate there is a significant difference in ethical judgment across career stages. Overall, it appears that practitioners in later career stages display higher ethical judgment than practitoners in lower career stages. Implications are provided for both practitioners and academicians.